2015
DOI: 10.1186/s12918-015-0183-x
|View full text |Cite
|
Sign up to set email alerts
|

Logical-continuous modelling of post-translationally regulated bistability of curli fiber expression in Escherichia coli

Abstract: BackgroundBacteria have developed a repertoire of signalling mechanisms that enable adaptive responses to fluctuating environmental conditions. The formation of biofilm, for example, allows persisting in times of external stresses, e.g. induced by antibiotics or a lack of nutrients. Adhesive curli fibers, the major extracellular matrix components in Escherichia coli biofilms, exhibit heterogeneous expression in isogenic cells exposed to identical external conditions. The dynamical mechanisms underlying this he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Even more intriguingly, we also observed a minor subpopulation of cells with high curli expression but low σ S activity. These results suggest that bimodality in curli expression arises due to the regulation downstream from σ S , most probably at the level of CsgD ( Grantcharova et al, 2010 ; Yousef et al, 2015 ), and that the curli-ON switch can be achieved already prior to the full activation of σ S . Notably, csgD expression is either directly or indirectly regulated by a number of cellular factors, including different transcription factors, levels of second messenger cyclic diguanosine monophosphate (cyclic di-GMP) and small regulatory RNAs (sRNAs) that mediate cellular responses to diverse environmental changes ( Gerstel and Römling, 2003 ; Jubelin et al, 2005 ; Pesavento and Hengge, 2009 ; Ishihama, 2010 ; Ogasawara et al, 2010a ; Liu et al, 2014 ; Michaux et al, 2014 ; Mika and Hengge, 2014 ).…”
Section: Discussionmentioning
confidence: 88%
“…Even more intriguingly, we also observed a minor subpopulation of cells with high curli expression but low σ S activity. These results suggest that bimodality in curli expression arises due to the regulation downstream from σ S , most probably at the level of CsgD ( Grantcharova et al, 2010 ; Yousef et al, 2015 ), and that the curli-ON switch can be achieved already prior to the full activation of σ S . Notably, csgD expression is either directly or indirectly regulated by a number of cellular factors, including different transcription factors, levels of second messenger cyclic diguanosine monophosphate (cyclic di-GMP) and small regulatory RNAs (sRNAs) that mediate cellular responses to diverse environmental changes ( Gerstel and Römling, 2003 ; Jubelin et al, 2005 ; Pesavento and Hengge, 2009 ; Ishihama, 2010 ; Ogasawara et al, 2010a ; Liu et al, 2014 ; Michaux et al, 2014 ; Mika and Hengge, 2014 ).…”
Section: Discussionmentioning
confidence: 88%
“…Direct interactions between PdeR and DgcM and their key functions for the molecular switch that turns on CsgD expression ( Fig. 1E ) have been previously analyzed in great detail ( 13 , 14 , 39 ). While it was clear that DgcE acts directly upstream of PdeR and provides the major positive input into this switch ( 13 , 17 , 20 ), the multiple direct protein interactions of DgcE in the c-di-GMP signaling supermodule indicate that this c-di-GMP input is specific and local also.…”
Section: Discussionmentioning
confidence: 99%
“…It is also conceivable that PdeR and DgcE could directly inhibit each other, which would contribute to the positive-feedback loops ( Fig. 1E ) that confer bistable switch properties to this system ( 39 ). Notably, DgcE is one of four DGCs that can interact with PdeR ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical modelling indicated that the DgcE/PdeR/DgcM/MlrA-mediated c-di-GMP control module can operate as a bistable switch [ 72 ]. The major ingredients generating such behaviour are two feedback loops that stabilize the OFF and ON states, respectively, in csgD transcription ( figure 2 ): (i) PdeR degrades the inhibitor, i.e.…”
Section: Pder: a Trigger Pde Throws The Switch To Turn On Biofilm Matmentioning
confidence: 99%